Insulin Autoimmune Syndrome in a 25-Year-Old, Previously Healthy Kuwaiti Man - Einas Alrashidi; Thamer Alessa (Case Reports in Endocrinology)
Insulin autoimmune syndrome (IAS) is a disease characterized by hyperinsulinaemic hypoglycaemia associated with autoantibodies against endogenous insulin. We have described a case of a 25-year-old, previously healthy Kuwaiti man who was admitted to the Mubarak Al-Kabeer hospital with a history of recurrent hypoglycaemia. The patient revealed that he had taken several different injectable anabolic steroids and growth hormone with oral amino acids and other tablets (fat burners) for bodybuilding in the last two months. He denied knowingly using insulin or insulin analogues. The patient had elevated fasting insulin level (>301 uIU/mL) and elevated insulin autoantibodies (>100.0 IU/mL). After appropriate work-up, he was diagnosed with IAS. After treatment with prednisolone (1 mg/kg/day), the patient had complete recovery. In patients with repeated hypoglycaemia, IAS should be considered in the differential diagnosis. Glucocorticoid therapy can be effective for the treatment of hypoglycaemia in patients with IAS.